2017
DOI: 10.1074/mcp.m116.064527
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for Protein Subcellular Localization: A Compartmental Map of the Rat Liver Proteome

Abstract: Accurate knowledge of the intracellular location of proteins is important for numerous areas of biomedical research including assessing fidelity of putative protein-protein interactions, modeling cellular processes at a system-wide level and investigating metabolic and disease pathways. Many proteins have not been localized, or have been incompletely localized, partly because most studies do not account for entire subcellular distribution. Thus, proteins are frequently assigned to one organelle whereas a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(92 citation statements)
references
References 52 publications
4
85
0
Order By: Relevance
“…A dual mitochondrial and peroxisomal localisation of MIRO1 was confirmed by immunofluorescence after expression of Myc‐MIRO1 in COS‐7 cells (Figure 1A). Furthermore, we previously reported endogenous MIRO1 in highly purified peroxisomal and mitochondrial fractions,34 in agreement with proteomics data 35, 36…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…A dual mitochondrial and peroxisomal localisation of MIRO1 was confirmed by immunofluorescence after expression of Myc‐MIRO1 in COS‐7 cells (Figure 1A). Furthermore, we previously reported endogenous MIRO1 in highly purified peroxisomal and mitochondrial fractions,34 in agreement with proteomics data 35, 36…”
Section: Resultssupporting
confidence: 85%
“…Furthermore, we previously reported endogenous MIRO1 in highly purified peroxisomal and mitochondrial fractions, 34 in agreement with proteomics data. 35,36 The targeting of all known TA proteins to peroxisomes requires the peroxisomal import receptor/chaperone PEX19. 34 For MIRO1, PEX19 binding was shown by immunoprecipitation after coexpression of Myc-MIRO1 and HA-PEX19 in COS-7 cells ( Figure 1B) suggesting a role for PEX19 in the targeting of MIRO1 to peroxisomes.…”
Section: Miro1 Is Dually Targeted To Peroxisomes and Mitochondriamentioning
confidence: 99%
“…In addition, TBCK was implicated in the mTOR pathway (Liu et al, 2013), which regulates lysosomal biogenesis and function (Kinghorn et al, 2017). Therefore, although subcellular localization analysis (Jadot et al, 2017) indicates that TBCK does not reside within the lysosome, these studies suggest that TBCK may control some aspects of lysosomal function and could result in phenotypes in CABMHF3.…”
Section: Loss-of-function Variants Outside Of Lsd Candidate Genesmentioning
confidence: 95%
“…Val181Leu mutation. SLC31A1 was targeted for analysis based on its dual localization to both the lysosome and to the plasma membrane, and we have reported previously on the variants in this patient (Jadot et al, 2017). While p.Arg90Ter is a clear null, further functional analysis to test the cellular copper uptake are necessary to demonstrate the effect of these two variants together.…”
Section: (4) 82rd265mentioning
confidence: 97%
“…It should be stressed that although luminal acidity stimulated lysosomal [ 3 H]glutamine uptake under the artificial conditions of our countertransport assay, our in situ TFEB-based assay clearly shows that SNAT7 operates in the export direction in live cells. A very recent proteomic study of multiple subcellular compartments from rat liver also identified lysosomes as the major, if not exclusive, cellular location of SNAT7 (38).…”
Section: Discussionmentioning
confidence: 99%